La capilla del hospital “Yurhixo” en Angahuan, Michoacán, México. Su antecedente técnico – arquitectónico y su proceso de restauración - Bedolla-Arroyo, J. A.; Alonso-Guzmán, E. M.; MartínezW.; Bedolla, E.; Chávez, H.; Lara-Gómez, C. (Revista ALCONPAT, 2014)
The old hospital chapel of "Yurhixo" in Angahuan, is an important part of the historical context of the buildings built during the early years of colonization in the Tarascan mountain range of the region of Michoacan, Mexico. This architectural building is an important sample of the sixteenth century hospital chapels, it shows the simplicity of architectural solution that met the needs of evangelization in the regions of the Columbian age. The research focuses on an analysis and registration of state of the chapel, identifying changes and materials deteriorations, giving an opinion of the state of conservation thereof and to propose a way of intervention of the building, in the proposed restoration activities concerning to consolidation of masonry exterior walls, cover of main facade, interior floors and coatings, and the complete restoration of the wooden structure, indicating a restoration process of the roof. Keywords: Historical monuments; restoration; hospital chapel.